Comparison of Acute Toxicity Test of Cardamom Extract Combination and Curcuma with a Combination of Cardamom Extract and Galangal against Artemia salina Leach by Brine Shrimp Lethality Test Method - Julian, Rixzal Azis; Desiani, Ekanita; Utami, Primanitha Ria (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
Cardamom, ginger, and galangal are one of the plants that are often used as herbal medicine. Similar studies that have been carried out previously only conducted single extract tests and have not combined extracts, and compared the results of using two combinations of extracts. However, because there is a possibility of interactions between compounds in a single extract that can increase their toxic effects, it is necessary to conduct acute toxicity testing of the combination aimed at determining the potential toxicity. This study aims to determine the comparison of the potential acute toxicity of cardamom and curcuma extract combinations with cardamom and galangal extract combinations seen from LC50 values using the Brine Shrimp Lethality Test (BSLT) method. The research conducted was an experimental study, extracted by maceration method and using BSLT method for toxicity testing. In this study using 5 variations in concentration, but the concentration of extracts used in the combination of extracts is different, namely the combination of cardamom and curcuma extracts using variations in concentrations of 12.5ppm, 25 ppm, 50 ppm, 100 ppm, while the combination of cardamom and galangal extracts uses variations in concentrations of 500 ppm, 250 ppm, 100 ppm, 50 ppm, 10 ppm. The LC 50 value was obtained from the number of larvae that died after 24 hours of treatment with probit analysis. The results showed that the combination of cardamom extract and curcuma had a highly toxic level against Artemia salina Leach larvae with an LC 50 value of 12.98 ppm, and a combination of cardamom extract (Amomum compactum Soland. ex Maton) and galangal (Alpinia galanga L) had an LC 50 of 18.08 ppm. The results showed that both combinations are highly toxic due to LC 50 ≤ 30 ppm values.